2014
DOI: 10.1111/inr.12141
|View full text |Cite
|
Sign up to set email alerts
|

Exploring faculty perceptions towards electronic health records for nursing education

Abstract: Electronic health records are significant applications of health information technology. Health informatics competency should be included as a required competency component in faculty professional development policy and programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…For example, in a dental simulation clinic, an e-Grading system was accessed through Web-based tablet devices at any time, and the system improved interaction between students and faculty. 34 Regarding the expected outcomes of AEMR use, participants emphasized the enhancement of nursing informatics competencies and critical thinking. Recently, academic education among healthcare professionals has considered the importance of competency-based education using technological innovations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a dental simulation clinic, an e-Grading system was accessed through Web-based tablet devices at any time, and the system improved interaction between students and faculty. 34 Regarding the expected outcomes of AEMR use, participants emphasized the enhancement of nursing informatics competencies and critical thinking. Recently, academic education among healthcare professionals has considered the importance of competency-based education using technological innovations.…”
Section: Discussionmentioning
confidence: 99%
“…[15] Kowitlawakul et al also reported that technology integration in nursing education has some challenges, but the pattern of challenges was not reported. [16] In general, Austria itemized technological delay, poor government support, inadequate exposure, and technological dependence as key problems users face while using ICT in nursing education. [14]…”
Section: Resultsmentioning
confidence: 99%
“…The most significant was the findings of Kowitlawakul et al who reported that nursing faculty members in Singapore consider technology integration in nursing education as innovative and of important value. [16] Austria also found that Filipino nursing students had positive attitude toward technology in nursing education, particularly in the practical demonstrations. [14]…”
Section: Resultsmentioning
confidence: 99%
“…Kowitlawakul, Chan, Wang, and Wang stated faculty member's attitudes and acceptance toward technology is critical in curricular integration of informatics. If faculty members do not use or accept technology, there will be a failure to produce nursing graduates with a minimum level of technological knowledge to provide safe and effective care [11].…”
Section: Problem Statementmentioning
confidence: 99%